Pengaruh Profitabilitas, Ukuran Perusahaan dan Struktur Modal Terhadap Manjemen Laba - Nuruddin, M Achmad; Rohmatunnisa, Layly Dwi (Akuisisi : Jurnal Akuntansi, 2023)
The purpose of this study was to determine the effect of profitability, company size and capital structure on earnings management in the company's financial statements. This survey uses data from 72 of 24 samples of companies listed on the Indonesia Stock Exchange between 2019 and 2021. This research uses quantitative research. The data used in this research is secondary data in the form of financial reports and annual reports. The statistical method used in this research is multiple regression method. Research result shows that profitability and firm size have a significant effect on earnings management, while capital structure has no significant effect on earnings management.